How Controls Improve Diagnostic Assay Performance: Hitchhiker's Guide to Diagnostic Assay Controls - Frank N. Martin; Ozgur Batuman; Douglas G. Luster; Timothy D. Miles; Yazmín Rivera; Poonam Sharma; David Geiser; Kitty Cardwell (PhytoFrontiers)
To have confidence that results from diagnostic assays for plant pathogens are accurate and to identify potential problems with false negatives and false positives, it is essential that the appropriate control reactions are included in the assay design. This review discusses control reactions that, depending on the technology used, should be either run in parallel or multiplexed with the diagnostic assay to ensure accuracy. The discussion includes immunoassays such as enzyme-linked immunosorbent assay and lateral flow devices, as well as molecular diagnostic techniques including PCR, isothermal technologies (recombinant polymerase amplification and loop-mediated isothermal amplification), and high-throughput sequencing. Additional details are provided for RNA virus assays that account for the need for a control reaction during the generation of complementary DNA. Although concepts of control reaction design and the reasons for their inclusion are discussed, the reader is directed to the Diagnostic Assay Validation Network website hosted on the American Phytopathological Society website for specific examples of control reactions reported in the literature that may be useful to consider when designing new diagnostic assays. [Figure: see text] Copyright © 2025 The Author(s). This is an open access article distributed under the CC BY-NC-ND 4.0 International license.